HEALTH WORKERS ENGAGEMENT: THE KEY OF EXCELLENCE SERVICE IN THE PRIVATE HOSPITAL - Tita Miawati; Didik Notosudjono; Widodo Sunaryo (International Journal of Economy, Education and Entrepreneurship, 2023)
In recent years, many studies on employee engagement have generated findings that engagement become an important factor in providing successful services to healthcare organizations. This study aims to find out the condition of health workers’ engagement in private hospitals and the role of organizational culture and servant leadership as drivers of employee engagement. The research sample of 118 frontline health workers had taken with a random sampling technique from health workers of two private hospitals in Indonesia. This study designed a survey method and used questionnaires to measure the strength of health workers' engagement, organizational culture, and servant leadership. The research findings generated some promising results that both the organizational culture of the hospital and the servant leadership of health workers' supervisors positively affect health workers' engagement. The role of organizational culture has a stronger effect on health workers' engagement than servant leadership. This research results recommended fostering work values in maintaining an organizational culture of the hospitals and increasing the spirit of service from the supervisor toward their employee subordinate